Molecular Evolution of Enterovirus 68 Detected in the Philippines - Imamura, Tadatsugu (Public Library of Science, 2013)
BACKGROUND: Detection of Enterovirus 68 (EV68) has recently been increased. However, underlying evolutionary mechanism of this increasing trend is not fully understood. METHODS: Nasopharyngeal swabs were collected from 5,240 patients with acute respiratory infections in the Philippines from June 2009 to December 2011. EV68 was detected by polymerase chain reaction (PCR) targeting for 5′ untranslated region (5′UTR), viral protein 1 (VP1), and VP4/VP2. Phylogenetic trees were generated using the obtained sequences. RESULTS: Of the 5,240 tested samples, 12 EV68 positive cases were detected between August and December in 2011 (detection rate, 0.23%). The detection rate was higher among inpatients than outpatients (p<0.0001). Among VP1 sequences detected from 7 patients in 2011, 5 in lineage 2 were diverged from those detected in the Philippines in 2008, however, 2 in lineage 3 were not diverged from strains detected in the Philippines in 2008 but closely associated with strains detected in the United States. Combined with our previous report, EV68 occurrences were observed twice in the Philippines within the last four years. CONCLUSIONS: EV68 detections might be occurring in cyclic patterns, and viruses might have been maintained in the community while some strains might have been newly introduced.